Dehydrogenation of N‐Heterocyclic Compounds Using H2O2 and Mediated by Polar Solvents. Issue 6 (18th February 2022) - Llopis, Natalia; Gisbert, Patricia; Baeza, Alejandro; Correa‐Campillo, Jara
Abstract: The oxidative dehydrogenation of N ‐heterocyclic compounds by using H2 O2 as oxidant in combination with polar solvents such as 1, 1, 1, 3, 3, 3‐hexafluoroisopropanol (HFIP) and H2 O is described. Among these two solvents, the best yields for the heteroaromatic compounds were generally achieved in HFIP. However, it is remarkable, that the use of a non toxic solvent such as H2 O gave such good yields. Furthermore, the procedure was implemented in larger‐scale and HFIP was distilled from the reaction mixture and reused (up to 5 cycles) without a significant detriment in the reaction outcome. Abstract :